(untitled) (Bangladesh Journal of Medical Physics, 2013)
Retention, absorbed dose, committed equivalent dose and committed effective doses have been assessed due to acute ingestion of 1 Bq of 60Co in human body. Calculations are done using Internal Radiation Dose Assessment (IRDA) software which has been developed based on the biokinetic model. Due to ingestion maximum radiation dose is deposited in the gastro intestinal (GI) tract, assumed to consist of four tissue compartments, e.g. stomach (ST), small intestine (SI), upper large intestine (ULI) and lower large intestine (LLI). In this work actual tissue masses of GI Tract of Bangladeshi people have been considered to calculate the above mentioned quantities for different age groups, such as 1 yr, 10 yrs and adult (female and male). One hour after the ingestion, the retention and absorbed dose show the trend ST > SI > ULI > LLI. Regarding tissue compartments the variation of the committed equivalent dose pattern is LLI > ULI > ST > SI for the radionuclide. The variation of absorbed dose, committed equivalent dose and committed effective dose with respect to age follow the pattern: 1 yr > 10yrs > adult female > adult male. The highest committed effective dose for ingestion of 1 Bq of the radionuclide under the study is found in the GI tract of 1 yr old child. This value is 6.56 x 10-6 mSv. For other age groups these values are slightly less. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14703 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 135-143